101 Oncological outcomes following risk reducing bilateral salpingo-oophorectomy in women deemed high risk for ovarian cancer. (13th November 2020) - Smallwood, K; Huang, V; Phillips, A; Crockett, S
Abstract : Introduction: This study aims to determine cancer rates following risk reducing bilateral salpingo-oophorectomy (BSO) in a high risk cohort. High risk women are those who carry an oncogenic gene mutation or have a strong family history of cancer. We aimed to establish the rate of both occult cancer and the precursor lesion serous tubal intraepithelial carcinoma (STIC). We also documented any subsequent diagnosis of primary peritoneal carcinoma (PPC). Methods: A retrospective study of 274 patients who underwent prophylactic BSO between January 2009 and January 2019 at the Royal Derby Hospital. Results: The median age at risk reducing surgery (RRS) was 47 (range 29 to 78). 151 patients (55%) were confirmed to have a high risk gene mutation. STIC was found in only one patient (0.3%) at RRS, however 3 further malignancies were diagnosed (1% of cases) one of which was tubal. Two patients subsequently developed PPC (0.7%), at 42 and 70 months respectively; neither of whom had STIC diagnosed at surgery. 99% of procedures were completed laparoscopically with a complication rate of 3%. Conclusion: Women with the BRCA gene or significant family history can carry up to a 50% lifetime risk of ovarian cancer. This study has shown that BSO reduces that risk to under 1%. Primary peritoneal carcinoma remains a risk despite surgery, and although it has been suggested that this may arise from a tubal precursor lesion (STIC), in our cohort, this was not isolated in either of the patients who developed PPC.